Pengaruh Lingkungan Sekolah dan Motivasi Belajar Terhadap Prestasi Belajar Ekonomi Siswa Kelas X dan XI Ips SMA Muhammadiyah 3 Surakarta Tahun Ajaran 2015/2016 - Purwaningsih, Rika (2016)
The purpose of this study are: 1) To determine the influence of the school environment on the learning achievement of the economy; 2) To determine the effect of learning motivation on learning achievement of the economy; 3) To determine the influence of the school environment and learning motivation on learning achievement economy. This research is a quantitative associative. The population in this study were all students of class X and XI IPS 3 SMA Muhammadiyah Surakarta academic year 2015/2016, amounting to 120 students with a sample of 100 students were taken by proportional random sampling technique. Data obtained by using questionnaires and documentation methods. Previous questionnaires have been tested and tested for validity and realibilitasnya. Data analysis technique used is lenier multiple regression analysis, t test, F test, the relative contribution and effective contribution. The results of the analysis of data obtained by linear regression line equation Y = 49 036 + 0,248X1 + 0,230X2. The conclusion that can be drawn from this study are: 1) no significant relationship between the school environment to the learning achievement of economic class X and XI IPS SMA Surakarta Muhammadiyah 3 Year 2015/2016. Based on t test obtained t> t table is 3.367> 1.985 (α = 5%) and the significance value <0.05 is 0.001; 2) there is a significant relationship between learning motivation towards learning achievement of economy class X and XI IPS SMA Surakarta Muhammadiyah 3 Year 2015/2016. Based on t test obtained t> t table is 3.745> 1.985 (α = 5%) and the significance value <0.05 is 0,000; 3) there is a significant relationship between the school environment and learning motivation on learning achievement of economic class X and XI IPS SMA Surakarta Muhammadiyah 3 Year 2015/2016. Based on test results obtained Fhitung F> Ftable is 15.668> 3.091 at a significance level of 5%; 4) variable X1 gives the relative contribution of 45.5% and the effective contribution of 11.1%, X2 gives the relative contribution of 54.5% and 13.3% effective contribution. The result of the calculation (R2) of 0.244, both total effective contribution of 24.4%, while 75.6% are influenced by other variables not examined.